Fatigue behaviour of 16Mo3 steel at elevated temperatures under uniaxial as well as biaxial‐planar loading. Issue 6 (29th November 2016) - Kulawinski, D; Hoffmann, M; Weidner, A; Lippmann, T; Lamprecht, G; Henkel, S; Biermann, H
Abstract: The isothermal fatigue behaviour of the ferritic steel 16Mo3 was investigated at 200 and 500 °C under uniaxial and biaxial‐planar loading. Furthermore, thermo‐mechanical fatigue behaviour under uniaxial loading was characterized under in‐phase (IP) and out‐of‐phase (OP) conditions between 200 and 500 °C. The fatigue lives of uniaxial and biaxial loading are in a good agreement to each other by using the distortion energy hypothesis according to von Mises. Under IP and OP thermo‐mechanical loading, nearly the same lifetimes were determined. They agree well with those of the isothermal tests at 500 °C. A recently developed fatigue lifetime model was applied on all tests and shows an excellent agreement within a scatter of two.